THE COGNITIVE APPROACH IN LANGUAGE TEACHING: INTERPRETATIONS AND IMPLEMENTATION CHALLENGES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article examines different interpretations of the cognitive approach in foreign language teaching. Four main interpretations are identified and analyzed: cognitive approach as conscious language learning, as application of cognitive linguistics, as integration of cognitive mechanisms at all learning stages, and as communicative-cognitive methods in modern textbooks. The study reveals inconsistencies between theoretical foundations and practical implementation, highlighting the need for clearer methodological frameworks.